2000
DOI: 10.1159/000014243
|View full text |Cite
|
Sign up to set email alerts
|

Brain Hemodynamic Changes in Preterm Infants after Maintenance Dose Caffeine and Aminophylline Treatment

Abstract: Objective: To investigate the acute effects of low-dose caffeine and aminophylline on cerebral blood flow in preterm infants, using both near-infrared spectroscopy (NIRS) and cerebral Doppler ultrasonography. Methods: Preterm infants with a gestational age of <32 weeks and birth weight of <1,500 g were randomized to receive either caffeine or aminophylline treatment for apnea of prematurity. The study period went from 30 min before to 60 min after the administration of the maintenance dose of pure caffeine (2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 22 publications
3
21
1
Order By: Relevance
“…Recent studies confirmed the validity of mixed cerebral oxygen saturation, measured by near infra-red spectroscopy, in monitoring brain oxygenation 22,23 and fixed 62% -75% as normal values in adults 24 and 40% as a normal value in fetuses 25 . Our data show that cerebral mixed cerebral oxygen saturation in healthy term infants is similar to those of preterm infants 26 and adults 24 . Finally, we reported the relative changes of oxidizedreduced cytochrome aa3.…”
Section: Discussionsupporting
confidence: 60%
“…Recent studies confirmed the validity of mixed cerebral oxygen saturation, measured by near infra-red spectroscopy, in monitoring brain oxygenation 22,23 and fixed 62% -75% as normal values in adults 24 and 40% as a normal value in fetuses 25 . Our data show that cerebral mixed cerebral oxygen saturation in healthy term infants is similar to those of preterm infants 26 and adults 24 . Finally, we reported the relative changes of oxidizedreduced cytochrome aa3.…”
Section: Discussionsupporting
confidence: 60%
“…[68] Controversy exists as to the effect of methylxanthines on CBF. According to a recent study, [69] caffeine does not affect cerebral hemodynamics to any great extent. Low doses of aminophylline increase cerebral blood volume and oxygenated hemoglobin transiently.…”
Section: Circulatory Endocrine and Metabolic Effects Of Methylxanthimentioning
confidence: 92%
“…Although the maintenance dose of caffeine does not affect cerebral hemodynamics [17] , each patient was studied at least 12 h after the administration of the last caffeine dose.…”
Section: Patientsmentioning
confidence: 99%